Blood cytotoxic/inflammatory mediators in non‐eosinophilic asthma. Issue 1 (January 2016) - Hodge, S.; Hodge, G.; Simpson, J. L.; Yang, I. A.; Upham, J.; James, A.; Gibson, P. G.; Reynolds, P.N.; ,
Summary: Background: Non‐eosinophilic asthma (NEA) is a distinct, often corticosteroid‐resistant inflammatory asthma phenotype. NK and NKT‐like cells are effector lymphocytes that we have shown, like CD28null T cells, to be relatively resistant to steroids and major sources of pro‐inflammatory/cytotoxic mediators. We hypothesized that these cells and mediators would be increased in peripheral blood in NEA. Methods: Adults with severe asthma and variable airflow obstruction, poorly controlled despite maintenance therapy with inhaled glucocorticosteroids and long‐acting bronchodilators, were recruited. Blood was assessed in those with eosinophilic asthma ( n = 12), NEA ( n = 25) and healthy non‐smoking controls ( n = 30). We applied flow cytometry to measure T, CD28null, NK and NKT‐like cells and their expression of granzyme B, perforin, and killer inhibitory/activating receptors CD94(Kp43), CD158b and CD107A. Intracellular pro‐inflammatory cytokine production (IFN‐γ and TNF‐α) was assessed in 18 controls and 10 patients with asthma/group. Results: In NEA, there was increased expression of granzyme B by CD8+ T cells vs. controls. There was increased expression of granzyme B and CD158 and decreased CD94 on NK cells, vs. healthy controls and those with eosinophilic asthma. IFN‐γ production by NK cells and TNF‐α production by NKT‐like cells in NEA were significantly increased vs. controls. In both eosinophilic and NEA phenotypes, there were significant increases in CD4+28null T cells (72% and 81% increases, respectively, vs. controls) and their expression of pro‐inflammatory cytokines. Significant correlations were noted between blood CD4+28null T cells and neutrophil numbers in induced sputum, and between corticosteroid dose and blood NKT‐like cells, and their production of granzyme B and TNF‐α and NK IFN‐γ. Conclusion and clinical relevance: In poorly controlled asthma, altered expression of cytotoxic/pro‐inflammatory mediators can be seen on a variety of lymphocyte subsets in the peripheral blood; these changes are most apparent in NEA. Whether this pattern of expression is a marker of treatment responsiveness and future risk of exacerbations remains to be determined.